Perception of creative economy in supporting family economy In Jayapura City.: (case study on culinary and craft subfields) - Iek, Mesak; Ratang, Sarlota Arrang (Advances in Social Sciences Research Journal, 2020)
Iek Mesak , Ratang sarlota, 2019, perception of creative economy in supporting family Peekonomian in Jayapura city. (case study on culinary and craft subfields) With 51 respondents creative economic actors on sub-fields of culinary and sub-field of crafts in Jayapura city. The purpose of this research is to analyze the perception of creative economic actors (Asar fish and noken bags) in supporting the family economy in Jayapura City., analyzing the influence of capital and Labor on the income of business actors (culinary target fish and A noken bag maker) in Jayapura City. The results of the study are: 1) for the characteristics of the respondent indicates that the average age of respondents showed that most at the age of 31 – 40 years as much as 30 respondents or 58.8%. It shows that the creative business in Jayapura is at a productive age. While seen from the most genders, women who do creative effort 40 respondents or 94.1%. This shows that women are a very important role in the creative business in Jayapura City. And the last is the type of business that is Almost balanced between the culinary creative effort one of them is the making of the target fish and from the side of the craft is making a noken bag. 2). For the factor that affects the income there are 2 namely capital and labor. And the analysis shows that the capital (X1) has a significant influence between the capital to the income of Business (Y).. While the workforce (X2) has a weak and insignificant impact on the income of businessmen